Design calculation of a membrane distillation crystallizer for water recovery from saline effluents with zero liquid discharge - Gaigher, Emanuelly Felix; Nariyoshi, Yuri (Brazilian Journal of Production Engineering, 2025)
Water scarcity is a global problem that has been intensifying, leading industries to seek strategies to reduce water intake and wastewater disposal. This work aims to create a crystallizer associated with membrane distillation for the recovery of water from saline effluents, with the goal of minimizing liquid waste. The optimization of the membrane distillation with crystallization (MDC) process was employed to enhance the recovery of water and salts. The proposed crystallizer was developed to work in synergy with the membrane module, enabling the efficient separation of water and salts as by-products. All obtained results are viable from an industrial standpoint, supporting this statement.